2011
DOI: 10.1111/j.1365-2672.2011.05135.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the germination of individual Clostridium perfringens spores and its heterogeneity

Abstract: Aims:  To analyse the germination and its heterogeneity of individual spores of Clostridium perfringens. Methods and Results:  Germination of individual wild‐type Cl. perfringens spores was followed by monitoring Ca‐dipicolinic acid (CaDPA) release and by differential interference contrast (DIC) microscopy. Following the addition of KCl that acts via germinant receptors (GRs), there was a long variable lag period (Tlag) with slow release of c. 25% of CaDPA, then rapid release of remaining CaDPA in c. 2 min (ΔT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
58
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(61 citation statements)
references
References 27 publications
3
58
0
Order By: Relevance
“…S4c and d). This suggests that sleC spores do not undergo any cortex hydrolysis process, similar to C. perfringens sleC mutant spores (41). It was also notable that the ⌬T release period for CaDPA in the wild-type spores that germinated was ϳ2.5 min, while for the sleC spores that germinated this value was much larger at ϳ40 min.…”
Section: Resultsmentioning
confidence: 76%
See 2 more Smart Citations
“…S4c and d). This suggests that sleC spores do not undergo any cortex hydrolysis process, similar to C. perfringens sleC mutant spores (41). It was also notable that the ⌬T release period for CaDPA in the wild-type spores that germinated was ϳ2.5 min, while for the sleC spores that germinated this value was much larger at ϳ40 min.…”
Section: Resultsmentioning
confidence: 76%
“…Previous work has found that bands from CaDPA dominate the Raman spectra of individual spores of Bacillus species and C. perfringens (23,41), and this was also the case for spores of two C. difficile strains (Fig. 1a).…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…This lag period is also seen in germination triggered by HP of ϳ150 megaPascals that activates GRs (43), as well as in germination with CaDPA and dodecylamine that trigger germination in a GR-independent fashion (4). Germination of spores of Clostridium perfringens with various germinants also exhibits this variable lag period (44). The length of the lag period in nutrient germination of spores of bacilli or C. perfringens is determined by multiple factors and is decreased by (i) increasing germinant concentration up to saturation, (ii) heat activation, and (iii) increased GR levels (4).…”
Section: Major Unanswered Questions About Spore Germination By Nutrientsmentioning
confidence: 99%
“…There are also some significant differences in the germination of spores of different clostridia, presumably because this is such an extremely diverse group of organisms (66). The similarities between nutrient germination of spores of clostridia and bacilli include the following: (i) spores of clostridia contain multiple SpoVA proteins that are essential at least for CaDPA uptake in sporulation, (ii) spores of clostridia most often contain GRs that are composed of subunits quite similar to those in spores of bacilli (6), and (iii) germination of individual C. perfringens spores in populations with nutrients, CaDPA, and dodecylamine exhibit the same varying lag periods seen during germination of spores of bacilli (44). However, there are also four major differences.…”
Section: Major Unanswered Questions About Spore Germination By Nutrientsmentioning
confidence: 99%